2021
DOI: 10.1002/aic.17368
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting accommodation microenvironment for Cu+ to enhance oxidation inhibition for thiophene capture

Abstract: Cu+‐containing materials have great potentials in various applications like adsorptive desulfurization. Nevertheless, their applications are severely obstructed by poor stability of Cu+ in air. Here, we first clarify the mechanism of Cu+ oxidation by first‐principle calculations and demonstrate that moisture accelerates Cu+ oxidation dramatically. Then, the microenvironment of Cu2O‐modified HKUST‐1, a typical metal‐organic framework, is adjusted from hydrophilic to hydrophobic with polydimethylsiloxane coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…3 Therefore, the development of high-performance adsorbents was indispensable to SADS technology. Even though a catalog of high-performance adsorbents, such as metal oxides, 4 molecular sieves, 5 porous carbon, 6 metal− organic skeleton (MOF), 7 and so on, has been developed so far, their separation from fuels after use is more difficult or causes serious loss, hindering their practical application. 8 Up to date, the transition metal Cu was assumed to be the distinguished adsorbing active species oriented to adsorption desulfurization due to the existence of interaction with S in aromatic sulfides through π-complexation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3 Therefore, the development of high-performance adsorbents was indispensable to SADS technology. Even though a catalog of high-performance adsorbents, such as metal oxides, 4 molecular sieves, 5 porous carbon, 6 metal− organic skeleton (MOF), 7 and so on, has been developed so far, their separation from fuels after use is more difficult or causes serious loss, hindering their practical application. 8 Up to date, the transition metal Cu was assumed to be the distinguished adsorbing active species oriented to adsorption desulfurization due to the existence of interaction with S in aromatic sulfides through π-complexation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nevertheless, Zhou’s work shows that hydrophobic ligands could not completely prevent crystal structure destruction due to water occupation. Jin et al and Li et al , demonstrated the feasibility of surface hydrophobicity modification of MOFs from hydrophilic to superhydrophobic by the chemical vapor deposition (CVD) of PDMS. At the same time, Guo et al prepared a high-performance composite, NbOFFIVE-1-Ni@PA, based on polyacrylate (PA).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] At present, the allowable S-content is restricted to 10 ppm or lower in many countries. [4][5][6] Further, S-free oil is vital in fuel cell development toward carbon emission abatement and neutralization. Hydrodesulfurization (HDS) is a conventional process for the removal of some S-components, for example, mercaptans, thioethers, and thiophenes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, fuel desulfurization is a must in petroleum refinery 1–3 . At present, the allowable S‐content is restricted to 10 ppm or lower in many countries 4–6 . Further, S‐free oil is vital in fuel cell development toward carbon emission abatement and neutralization.…”
Section: Introductionmentioning
confidence: 99%